Emerging trends and new developments in Lancang‐Mekong River: A bibliometric visualization analysis. (7th March 2020) - Junlin, Ren; Ziqian, Peng; Xue, Pan
Abstract: The purpose of this study is to outline global performance, and to quantitatively evaluate the current research field hot spots, and the future trends about the Lancang‐Mekong River (LMR). Bibliometric methods are used to analyze 3, 924 records retrieved from the collection of the Web of Science Core (WoS). The performance of publications, categories, countries, institutes, research hot spots and trends is analyzed in this study by applying CiteSpace and VOSviewer tools. The results revealed that publications about the LMR field have been increasing rapidly since the beginning of the 21st century. The research pertaining to LMR is mainly in the fields of environmental sciences & ecology, water resources, geology, engineering and agriculture. Vietnam, The People's Republic of China, The United States of America, Japan and Thailand get higher rankings in paper output, and Can Tho University, the Chinese Academy of Sciences, Beijing Normal University and the University of Tokyo achieve a high ranking on LMR research. In addition, further studies in research frontiers have revealed that health, security, climate change and international waters will become the new and popular directions and trends in the LMR research.